2002
DOI: 10.2307/3061038
|View full text |Cite
|
Sign up to set email alerts
|

Peak Fire Temperatures and Effects on Annual Plants in the Mojave Desert

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecological Applications. Abstract. Very little is known about the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 22 publications
2
39
2
Order By: Relevance
“…Bromus madritensis abundance was dramatically reduced by the fire, but Schismus spp. and Erodium cicutarium benefited, similar to other studies (Minnich & Dezzani 1998; Brooks 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Bromus madritensis abundance was dramatically reduced by the fire, but Schismus spp. and Erodium cicutarium benefited, similar to other studies (Minnich & Dezzani 1998; Brooks 2002).…”
Section: Discussionsupporting
confidence: 90%
“…However, some trends appeared from the collective results of individual studies. First, several studies reported a strong temporal influence (linked to precipitation) on the reestablishment of annual plants, where rainfall amounts in a given year could overwhelm any effects of disturbance (e.g., [53,60,76]). In some years of low rainfall virtually no annuals may be recorded, whereas in moist years, biomass and cover may increase several orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…In some years of low rainfall virtually no annuals may be recorded, whereas in moist years, biomass and cover may increase several orders of magnitude. Second, Brooks [60] and Cave and Patten [72] highlighted the effects of microsite (e.g., below shrubs versus in interspaces between shrubs) on the distribution and abundance of annual plants in both disturbed and undisturbed areas. Overall, annual plants were more abundant below shrubs in both areas, but some annual species showed contrasting patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations